Unilateral calf hypertrophy and focal myositis induced by S1 radiculopathy: dramatic response to steroid treatment. (30th September 2013) - Hemmi, Shoji; Shirakawa, Shunichi; Kurokawa, Katsumi; Sunada, Yoshihide
Abstract : Unilateral enlargement of the calf in a 57-year-old man with S1 radiculopathy is described in this case report. Short tau inversion recovery-weighted imaging provided evidence of selective hypertrophy and a high signal intensity of the gastrocnemius and soleus. Histopathological analysis of the gastrocnemius revealed an endomysial inflammatory infiltrate and marked denervation lesions. Marked signs of denervation are suggestive of focal myositis secondary to neurogenic damage. The patient was treated with an oral corticosteroid (30 mg/day) and the calf hypertrophy was dramatically reduced within 5 weeks. Our case indicates that steroid therapy should be tried because it may be a potentially treatable disease.